ANALYSIS OF DETERMINING PERMANENT EMPLOYEES USING OCRA (OPERATIONAL COMPETITIVENESS RATING ANALYSIS) METHODOLOGY - Darniati; Nurahmad, Nurahmad; Mulyadi, Ida Mulyadi; Musdalifa Thamrin; Samsuria, Samsuria; Muhammad Faisal (Yayasan Nusantara Hasana Berdikari, 2024)
The determination of permanent employees is a crucial strategic decision for every organization. This decision affects productivity, efficiency, and work culture within the company. This study aims to analyze and determine permanent employees using the OCRA (Operational Competitiveness Rating Analysis) Method. OCRA is a method that assesses employee performance based on indicators of Length of Work, Work Loyalty, Age, Last Education, Work Performance, Communication Skills, and Teamwork Skills that are relevant to the operations of a company. In this study, employee performance data is collected and analyzed using a quantitative approach. Each employee is assessed based on a number of criteria that include productivity, quality of work, compliance with procedures, and contribution to the team and the company as a whole. The results of the OCRA analysis are then used to identify employees who have superior performance and deserve to be considered as permanent employees. The results of the study show that the OCRA Method is able to provide an objective and measurable assessment in determining permanent employees. A3-employees with the highest OCRA scores are proven to have consistent performance and a significant contribution to the achievement of company goals. This study concludes that the use of the OCRA Method in determining permanent employees can increase transparency and accuracy in human resource management decision-making.